Influencia del juego en el desarrollo integral de los niños de la Unidad Educativa Cleopatra Fernández de Castillo, de la ciudad de Machala, periodo 2014-2015. - Reyes Espinoza, Mercy Germania (2015)
In the early years of life, a timely and relevant attention has effects of great impact for children. Several studies have shown that interactions which provide children with classmates study, have fundamental consequences for brain development. But these educational experiences should involve other factors such as health care and good nutrition, as essential complements to achieve adequate child development.